MONITORING DAN EVALUASI PROJECT PA FLOW PLTU KEBAN AGUNG PADA BIDANG BUSINESS DEVELOPMENT DI PT PLN NUSANTARA POWER SURABAYA - Erwina Putrikuri, Kharisma; Rusdianto, Yuniardi (PT Naureen Digital Education, 2025)
This research aims to analyze the monitoring and evaluation of the PA Flow project at PLTU Keban Agung in the Business Development Division of PT PLN Nusantara Power Surabaya. Monitoring and evaluation in MRO units plays an important role in the context of electricity generation. Through case studies and data analysis, this research identifies areas of improvement and proposes corrective actions to improve the service quality of the MRO unit. The results provide in-depth insight into the importance of monitoring and evaluating the PA Flow PLTU Keban Agung project in the Business Development Generation Derivatives Sector at PT PLN Nusantara Power.